Physical activity and type 2 diabetes mellitus risk: population studies review - Sergey N. Bogatyrev (Сахарный диабет)
Physical activity is one of the most important components of a healthy lifestyle. Regular physical activity helps to maintain normal blood glucose levels and reduce the risk of type 2 diabetes mellitus. This review presents population studies investigating physical activity as a factor for type 2 diabetes mellitus risk. A search using the keywords ‘physical activity’, ‘type 2 diabetes mellitus’ and ‘risk’ identified more than 40 relevant original studies and meta-analyses, which are presented in this review. Different types of physical activity have positive protective effects on type 2 diabetes mellitus risk and reduce the risk of death in patients with type 2 diabetes mellitus.